Clinical implementation of an emergency department coronary computed tomographic angiography protocol for triage of patients with suspected acute coronary syndrome - Ghoshhajra, Brian B.; Takx, Richard A. P.; Staziaki, Pedro V.; Vadvala, Harshna; Kim, Phillip; Neilan, Tomas G.; Meyersohn, Nandini M.; Bittner, Daniel; Janjua, Sumbal A.; Mayrhofer, Thomas; Greenwald, Jeffrey L.; Truong, Quyhn A.; et al. (European Radiology, 2017)
OBJECTIVES: To evaluate the efficiency and safety of emergency department (ED) coronary computed tomography angiography (CTA) during a 3-year clinical experience. METHODS: Single-center registry of coronary CTA in consecutive ED patients with suspicion of acute coronary syndrome (ACS). The primary outcome was efficiency of coronary CTA defined as the length of hospitalization. Secondary endpoints of safety were defined as the rate of downstream testing, normalcy rates of invasive coronary angiography (ICA), absence of missed ACS, and major adverse cardiac events (MACE) during follow-up, and index radiation exposure. RESULTS: One thousand twenty two consecutive patients were referred for clinical coronary CTA with suspicion of ACS. Overall, median time to discharge home was 10.5 (5.7-24.1) hours. Patient disposition was 42.7 % direct discharge from the ED, 43.2 % discharge from emergency unit, and 14.1 % hospital admission. ACS rate during index hospitalization was 9.1 %. One hundred ninety two patients underwent additional diagnostic imaging and 77 underwent ICA. The positive predictive value of CTA compared to ICA was 78.9 % (95 %-CI 68.1-87.5 %). Median CT radiation exposure was 4.0 (2.5-5.8) mSv. No ACS was missed; MACE at follow-up after negative CTA was 0.2 %. CONCLUSIONS: Coronary CTA in an experienced tertiary care setting allows for efficient and safe management of patients with suspicion for ACS. KEY POINTS: • ED Coronary CTA using advanced systems is associated with low radiation exposure. • Negative coronary CTA is associated with low rates of MACE. • CTA in ED patients enables short median time to discharge home. • CTA strategy is characterized by few downstream tests including unnecessary ICA.
EVALuna2:33636